#TITLE_ALTERNATIVE# - HALIM (NIM : 12208029), HAMDI
Coalbed methane (CBM) is one of the unconventional gas which main composition is methane. CBM is produced from coal layer, unlike the conventional gas which is generally produced from sandstone or limestone. CBM reservoir, simultaneously acts like source rock and storage reservoir. Methane gas is adsorbed in the matrix of coal which is formed during the coalification process. CBM is produced by dewatering process, that is producing the water filled in the cleats to decrease reservoir pressure until desorption pressure is reached. Once desorption pressure is reached, methane released from coal matrix surface and flows through micropore to natural fractures towards the wellbore. This period of water producing is called dewatering time. Dewatering time depends on to its reservoir and coal properties and bottomhole pressure. Dewatering time prediction is very important for developing CBM project because this period of time will affect the value of the project. To predict dewatering time, a reservoir engineer occasionally use reservoir simulation. However, this method is considered costly. Therefore, this study will discussed an alternative method to predict the dewatering time in form of equations as a function of its reservoir and coal properties and bottomhole pressure.